Behavioral and psychological correlates of problematic smartphone use in street ketamine users - Chia-Heng Lin; Yang-lin Lin; Chia-Hsiang Chan (BMC Psychology)
Abstract Background While problematic smartphone use screening tools are widely used and increasingly evaluated in student populations, their applicability and clinical stability across diverse groups—particularly those with comorbid substance use—remain unclear. Moreover, the overlap between problematic smartphone use and internet gaming disorder has not been well established in clinical contexts. This study explores the behavioral and psychological characteristics associated with problematic smartphone use, focusing on its relationship with online gaming behaviors among ketamine users referred for court-ordered addiction treatment. Methods The study involved 233 participants diagnosed with ketamine use disorder. Participants reported their daily smartphone use and primary usage purposes. Ketamine dependence was assessed using the Chinese version of the Severity of Dependence Scale. Emotional distress was evaluated using the Brief Symptom Rating Scale and Generalized Anxiety Disorder 7-Item Scale. Attention-deficit/hyperactivity disorder (ADHD) symptoms were assessed using the Adult ADHD Self-Report Scale (ASRS-V1.1). Problematic smartphone use risk was evaluated using the Short Form of the Problematic smartphone use Inventory (SPAI-SF). Logistic regression was used to analyze factors related to problematic smartphone use risk. Results The problematic smartphone use risk group reported significantly longer daily smartphone usage (odds ratio [OR]: 1.64; 95% confidence interval [CI]: 1.29–2.08), higher ASRS-V1.1 scores (OR: 1.14; 95% CI: 1.05–1.23), and a greater likelihood of using smartphones for online gaming (OR: 2.26; 95% CI: 1.19–4.29). Conclusions Excessive smartphone use in ketamine users is closely linked to online gaming, and ADHD symptoms may increase the risk of problematic smartphone use in this population.